Jazz, Africa and creolization: about Herbie Hancock. Interview with French Jazzman Bernard Lubat. - (:unkn) unknown (My University, 2008)
The question of the relationship between jazz and Africa is not only that of the "African origins of jazz," but also concerns the possibilities of encounters today between jazz and African music. It is from this angle that we approach it here through the feelings of a particular jazz musician, Bernard Lubat. During this interview, we analyze different examples of jazz and African music, on the one hand, fusion experiments led by Herbie Hancock and on the other, excerpts from traditional African repertoires. For the former, we will study the type of encounters that are actually implemented, and for the latter, those that could be imagined. In each case, we will question the conditions allowing us to speak of creolization with regard to these encounters.
Keywords: African Research